Kompleksitas Regulasi Administrasi Keimigrasian dan Dampaknya terhadap Layanan Publik - Daffa Raihan Arya Mas’adi (BADAN PENERBIT STIEPARI PRESS, 2026)
Immigration administration is one of the important instruments in modern governance that is directly related to cross-border human mobility. This research aims to explore the complexity of immigration administrative regulations in Indonesia and their impact on the quality of public services. The complexity of regulations is reflected in the fragmentation of policies, layered bureaucracy, and implementation gaps that cause services to be slow, inefficient, and prone to multiple interpretations. This research uses a descriptive qualitative method with a literature study approach, examining laws and regulations, legal documents, and relevant academic literature. The analysis was carried out with content analysis and a normative approach to assess the suitability between legal norms and implementation in the field. The results of the study show that overlapping regulations and weak coordination between agencies create legal uncertainty, reduce accountability, and weaken public trust in immigration institutions. In addition, a layered bureaucracy causes service distortions in the form of inefficiencies, corruption opportunities, and limited transparency. To overcome these problems, regulatory reform is needed that emphasizes cross-sector harmonization, strengthening the capacity of apparatus, utilizing digital technology, and improving accountability mechanisms and community participation. This reform is expected to be able to realize public services in the field of immigration that are simpler, responsive, and with integrity.